Acute Fever with Painful Swelling of Leg in Alcoholic Cirrhosis Patient - Lerwiwattaworn, Sarut (Greater Mekong Subregion Medical Journal, 2024)
Patients with liver cirrhosis are susceptible to bacterial infection. The common infection sites are spontaneous bacteremia, urinary tract infection, pneumonia, soft tissue infection and spontaneous bacterial peritonitis. Gram-negative bacteria such as Escherichia coli and Klebsiella spp. were the most common microorganisms causing bacteremia in cirrhotic patients. Vibrio, Aeromonas, and Campylobacter spp. occasionally caused bacteremia in cirrhotic patients, but these individuals are at great risks for invasive infections. The vibrios are found in marine and surface waters. Aeromonads are inhabitants of aquatic ecosystems, worldwide, and are found in fresh and brackish waters. The campylobacters are found in many species of animals, including many domesticated animals. Here we report a case of soft tissue infection from Aeromonas hydrophila in liver cirrhosis patient which caused rapidly progressive septicemia and shock.